The art of falling: identifying the falls scenarios associated with bouldering injuries - Erwan Beurienne; Erwan Beurienne; Nicolas Bailly; Maxime Luiggi; Maxime Luiggi; Cécile Martha; Claire Bruna-Rosso; Maxime Wylomanski; Michel Behr; Marine Dorsemaine (Frontiers in Sports and Active Living)
IntroductionBouldering has seen a significant rise in popularity, accompanied by an increase in related injuries, primarily caused by falls. To enhance prevention strategies and improve protective mats, it is crucial to understand the mechanisms behind these injuries. However, there is limited knowledge about the specific fall scenarios leading to bouldering injuries. The aim of this study was to provide a detailed description of accident scenarios and fall kinematics leading to bouldering injuries.MethodsAdults (aged 18 and above) who experienced an acute fall-related injury while bouldering were invited to complete a self-reported online survey. They were recruited between February 2024 and March 2025 through emails and QR-code posters via university mailing lists and partnerships with French bouldering gym franchises. A total of 245 participants provided personal information, descriptions of their injuries, details about the climbing routes, and fall scenarios, including the kinematics of the fall.ResultsA majority of the injuries affected the lower limb (67% of the case) with ankle sprain being the primary injury. Most of the falls (85%) were involuntary with 62% of them starting in a vertical position, frequently followed by a rotation during the fall (62%), and resulted in a feet first landing (74%). Most injuries happened after falls from vertical walls (45%) and steep walls (29%), primarily from the middle (32%) and the top (47%) sections of the wall.ConclusionThese results provide a first detailed description of the fall scenarios associated with injuries in bouldering and show that different injury mechanisms (such as vertical versus leaning positions during a fall) result in distinct patterns of injury. Such findings could be used to develop new pads with higher density or multi-layering, or to devise safer falling techniques that can be taught by trainers.